The impact of circadian rhythm on Bacillus Calmette-Guérin vaccination effects on SARS-CoV-2 infections - Föhse, Konstantin; Taks, Esther J.M.; Moorlag, Simone J. C. F. M.; Bonten, Marc J. M.; van Crevel, Reinout; ten Oever, Jaap; van Werkhoven, Cornelis H.; Netea, Mihai G.; van de Maat, Josephine S.; Hoogerwerf, Jacobien J. (Frontiers in Immunology, 2023)
Background and objective: A recent study has suggested that circadian rhythm has an important impact on the immunological effects induced by Bacillus Calmette-Guérin (BCG) vaccination. The objective of this study was to evaluate whether the timing of BCG vaccination (morning or afternoon) affects its impact on severe acute respiratory syndrome–coronavirus-2 (SARS-CoV-2) infections and clinically relevant respiratory tract infections (RTIs). Methods: This is a post-hoc analysis of the BCG-CORONA-ELDERLY (NCT04417335) multicenter, placebo-controlled trial, in which participants aged 60 years and older were randomly assigned to vaccination with BCG or placebo, and followed for 12 months. The primary endpoint was the cumulative incidence of SARS-CoV-2 infections. To assess the impact of circadian rhythm on the BCG effects, participants were divided into four groups: vaccinated with either BCG or placebo in the morning (between 9:00h and 11:30h) or in the afternoon (between 14:30h and 18:00h). Results: The subdistribution hazard ratio of SARS-CoV-2 infection in the first six months after vaccination was 2.394 (95% confidence interval [CI)], 0.856-6.696) for the morning BCG group and 0.284 (95% CI, 0.055-1.480) for the afternoon BCG group. When comparing those two groups, the interaction hazard ratio was 8.966 (95% CI, 1.366-58.836). In the period from six months until 12 months after vaccination cumulative incidences of SARS-CoV-2 infection were comparable, as well as cumulative incidences of clinically relevant RTIs in both periods. Conclusion: Vaccination with BCG in the afternoon offered better protection against SARS-CoV-2 infections than BCG vaccination in the morning in the first six months after vaccination.